Unintended consequences [compact disc, unabridged] : why everything you've been told about the economy is wrong - Conard, Edward (Blackstone Audio, 2012)
Many commonly held beliefs have emerged to explain the cause of the financial crisis. Conventional wisdom blames Wall Street and the mortgage industry for using predatory tactics to seduce unsuspecting home owners and blames average Americans for borrowing recklessly and spending too much. Conventional wisdom masks the real causes of our economic disruption and puts us at risk for unintended and potentially dangerous consequences.